Participatory research with coffee growers in regards to the coffee berry borer management Hypothenemus hampei (Coleoptera: Scolytidae) in the post harvests - SALAZAR-E., HUGO MAURICIO; ARISTIZÁBAL-A., LUIS FERNANDO; GONZALO-MEJÍA, CARLOS (Revista Colombiana de Entomología, 2003)
A participatory research diagnosis with small coffee growers in nine veredas of Caldas, Quindío and Risaralda departments was carried out in 1998. The aim of this research was to evaluate the post• harvest control of coffee berry borer (CBB). Before starting with the project, 93% of the coffee growers did not practice any control in the process of coffee gain. Eighteen months later, 79% of them used to control over the coffee berry borer. The technique used involved a plastic lid covered with grease used in both the receiving portion and the coffee pulp. 72% of the coffee growers constructed the covered lid. On average the covered lid had an area of 3 m2. The coffee growers carried out 903 evaluations of CBB captured on the covered lids. On average each CG performed 20 evaluations of postharvest CBB control. The total number of CBB captured was estimated at 948.723, an average of 7714 CBB captured. The cost of the covered lid was almost 5.0 US dollars. After the CG got together to evaluate the results, they realized that it is very important to perform the postharvest CBB control practices. Also, they made some comments about the advantages of this practices such as: «the plastic cover lid is very useful to capture CBB, they are very cheap and they avoid the coming back of CBB to the coffee plantation and if this happens the CBB is going to damage the forthcoming production». «The postharvest practice is essential to control CBB», «They are very good to capture CBB» and « the kill cover lid is a very good invention».